O IDEB COMO PARÂMETRO DE QUALIDADE DA EDUCAÇÃO BÁSICA NO BRASIL: algumas preocupações - Luiz Carlos Gesqui (Cadernos de Pesquisa, 2016)
: The search for the definition of elements that establish minimum standards which would consist quality of the national basic education occupied a prominent place in the Brazilian educational field for decades. This article aims to highlight that the National Education Plan (PNE) 2014-2024 discourages this search to legally establish the Basic Education Development Index (IDEB) as a quality parameter of the national basic education. To develop this argument are analyzed in a first procedure, academic productions that precede the current PNE and who has study object the use of statistical indicators in the educational field. In a second procedure it has been analysed the goal 7 of the current PNE and some of their strategies comparing them with results of recent research whose objectives are similar to the objectives proposed by these strategies. The results of analyzes indicate a wide disregard of academic production related to the quality of the elaborate education in the period before approval of the current PNE and that some school practices whose goals are similar to those proposed by the strategies analyzed goals has produced outcomes that do not contribute to improving the quality of basic education.